Mercury Determination Using Stannous Chloride Reductant Followed by Atomic Absorption Spectrometric Measurement: Performance Characteristics, Uncertainty Estimation, and Compliance Assessment - Yohanes Susanto Ridwan; Tiny Agustina Koesmawati; Anna Edy Persulessy; Raden Tina Rosmalina; Astried Sunaryani; Fitri Dara (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Indonesian government has committed to reduce and eliminate mercury. Hence, the intensity of monitoring activities of mercury levels in various matrices would be increased and supported by qualified analytical data. Key characteristic performances, i.e., the limit of detection, linear range, precision, trueness, have been successfully carried out, and the method was shown to fit the purpose. The limit detection, LoD and LoQ, were found to be 0.26 and 0.86 µg/L, respectively, which were adequate to reach the tightest regulatory limit of mercury in surface water (1 µg/L). The examined linearity range of 1-20 µg/L has been found sufficient for its application since a high mercury concentration in the typical sample is seldomly expected. Precision and trueness aspects of the method were shown to have satisfaction performance, with CV of 1,24% and recovery of 104.54%. All the possible uncertainty sources have been identified in this study. Since no reference material was available, the uncertainty of bias was evaluated through the recovery of the spiked sample. Compliance assessment to six measurement results has been performed; one result was below LoQ, four were clearly below regulatory limit, and one was questionable. Hence a decision rule was applied.